Design and validation of brucellosis prevention questionnaire focused on animal vaccination - Farhad Bahadori; Fazlollah Ghofranipour; Saeideh Ghaffarifar; Reza Ziaei (BMC, 2021)
Abstract Background The inadequate awareness of livestock breeders on brucellosis transmission, as well as their improper knowledge about preventing brucellosis is considered as one of the important barriers to animal vaccination against brucellosis. The present study aimed to design and validate a brucellosis prevention questionnaire focused on animal vaccination. The valid questionnaire was used to design, implement, and evaluate an interventional training program. Method A brucellosis prevention questionnaire (BPQ) was developed in the exploratory psychometric study. In addition, face-to-face interviews were conducted to formulate its initial items, the results of which were merged with those obtained from literature review. Further, the face, content, and construct validity of the questionnaire were assessed by co-operating livestock breeders, veterinarians, and health educationists. The impact score (IS), and content validity ratio (CVR) and index (CVI) of the items were calculated, and the construct validity of the questionnaire was evaluated through factor analysis. Furthermore, the reliability of the results related to the questionnaire was measured by using Cronbach's alpha, intra-class correlation coefficient (ICC), and composite reliability, as well as the standard error of measurement (SEM). Results The questionnaire was finalized with 53 items and its validity was confirmed by CVI (0.90), CVR (0.74), and IS (4.30). Additionally, the items were loaded into three constructs of awareness, attitude, and practice. Further, the predictive power of awareness, attitude, and practice was determined as 43.43, 15.81, and 15.78%, respectively. Furthermore, the fitness of the proposed model among the constructs was confirmed by the root mean square error of approximation (RMSEA) < 0.08, as well as normed chi-square (× 2/ df) < 5.0, comparative fit index (CFI) ≥ 0.90, and Tucker- Lewis index (TLI) ≥ 0.9. Conclusion The brucellosis prevention questionnaire represented acceptable psychometric properties. The factors influencing the preventive behavior of livestock breeders can be identified by applying the questionnaire, and co-operating veterinarians and educational planners.